Temperature dependence of hot luminescence in solid xenon: theory and experiment: Spectroscopy in Cryocrystals and Matrices - Selg, Matti; Kink, Rein (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Vibrational relaxation of self-trapped excitons in solid xenon has been investigated both experimentally and theoretically. Hot luminescence spectra of the crystal have been measured in a wide temperature range (from liquid helium temperature to 100 K), using x-ray and two-photon excimer laser (ArF and KrF) excitation. The theoretical analysis is based on a recent nonperturbative relaxation theory and on a rigorous quantum mechanical Franck—Condon approach.